Analisis Prosedur Administrasi Peralihan Hak Atas Tanah Hibah pada Kementerian Agraria dan Tata Ruang / Badan Pertanahan Nasional Kabupaten Bungo Provinsi Jambi - Mardansyah - (Dialektika Publik, 2020)
This research was conducted due to several problems including: the absence of efforts to transfer land rights according to clear procedures and conditions, the absence of legal certainty and protection for holders of land rights grants. This research was conducted on 20 people involved in the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency Bungo Regency of Bungo Regency using a survey method with a descriptive qualitative approach. The results of the research show the procedures for administering the transfer of rights to land grants at the Ministry of Agrarian Affairs and Spatial Planning. Procedures for administering the transfer of land rights to the grant, for land that has been certified by the grantee and the grantee before the official land deed maker (PPAT) to sign the grant deed. In the process of making a grant deed, the grant giver must complete land data and data on the grantee and recipient of the grant. Obstacles to the Office of the Ministry of Agrarian Affairs in the Transfer of Rights to Land Grants is the high number of people who do not understand about the transfer of rights to land grants, underutilized office facilities and infrastructure, lack of employee discipline.